Receitas familiares de mulheres das praias do Cumbuco e de Tabuba-CE: identificação de atributos culturais e emocionais baseados na alimentação - Bastos, Regina Maria Silva (2024)
This research compiles culinary recipes from residents of the beaches of Cumbuco and Tabuba CE, characterizing them in terms of memory and cultural, traditional, and emotional attributes. To conduct the study, it was necessary to identify culinary recipes presented by these residents, particularly from fishing families in Praia do Cumbuco-CE and neighboring areas; analyze the recipes and compare them with the aspects of memory shared by the study participants; identify the traditional or emotional attributes of the recipes presented in the study; and conduct a sensory analysis of the recipes mentioned by the participants regarding their liking/acceptance, using sensory memory. Sixteen (16) participants, all residents of the western coast of Ceará state, specifically from Praia do Cumbuco and surrounding areas, were interviewed. In this context, the need arose to identify which foods are remembered by the residents of this community. The interviews were conducted in person and supported by a questionnaire with questions that enabled the identification and analysis of the recipes informed by the participants concerning memory and their traditional and emotional attributes. This is a qualitative and descriptive study. As a result, it was found to be feasible to evaluate preparations based on sensory memory through the application of sensory methodologies. In conclusion, culinary recipes from residents of Praia do Cumbuco-CE were compiled, characterized by memory and their cultural, traditional, and emotional attributes. This research aims to contribute to tourism, which is very strong in Praia do Cumbuco, and to the documentation of knowledge and practices rooted in traditional knowledge.